2007
DOI: 10.1002/ieam.5630030311
|View full text |Cite
|
Sign up to set email alerts
|

The sediments of the venice lagoon (Italy) evaluated in a screening risk assessment approach: Part II—lagoon sediment quality compared to hot spots, regional, and international case studies

Abstract: The objective of this study was to carry out a critical comparison of data on the screening quality of surface sediments in Venice Lagoon (VL; main lagoon and its subbasins, Porto Marghera [PM], and Venice City Canals) and in other transitional and coastal ecosystems with various levels of human impact (urbanization and industrialization). To put VL in terms of reference and industrialized sites in the region, case studies were selected from the North Adriatic Region; to gain insight into how VL sediments comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Figures 6 and 7 clearly show also how the 2 hot spots in the lagoon, PM and Venice City canals, significantly differ from the open lagoon. These 2 sites are discussed in greater detail in the companion paper (Apitz, Barbanti, et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figures 6 and 7 clearly show also how the 2 hot spots in the lagoon, PM and Venice City canals, significantly differ from the open lagoon. These 2 sites are discussed in greater detail in the companion paper (Apitz, Barbanti, et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in the contour plots in Figures 2 and 3, sediment contaminant levels are highly heterogeneous in most areas of the lagoon and there are large ranges between the minimum and maximum values in each area (Table 4). Examination of the raw data (see Apitz, Barbanti, et al 2007) for a graphical view of the data ranges, means, and media) revealed that, in most cases, the mean sediment chemistry values also are much higher than the median values, suggesting that the means are dominated by the few hot spot areas in a region. However, because dredging projects and other potential activities can span large and heterogeneous areas, hot spot data were not treated as outliers to be removed from the dataset, but as part of the data range that represents the range of sediment quality in the regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations